SOYBEAN (GLYCINE MAX L. MERILL) GENETIC IMPROVEMENT IN ETHIOPIA: A REVIEW - Getnet, Besufikad Enideg (International Journal of Research -GRANTHAALAYAH, 2019)
Soybean is an economically important leguminous crop. Genetic improvements of the crop have focused mainly on enhancement of seed and oil yield, development of varieties suited to different cropping systems and locations, and breeding resistant/tolerant varieties for various biotic and abiotic stresses. The concept surrounding genetic improvement of soybean has the potential to impact all aspects of the crop. Resistance to biotic and abiotic factors have a profound impact on production, quality, crop values and profitability. Plant breeders have used conventional breeding techniques for the improvement of these traits in soybean. The conventional breeding process can be greatly accelerated through the application of molecular and genomic approaches. Since the inception of soybean breeding in Ethiopia in the 1950s a remarkable success has been achieved in increasing its yield and developing varieties which fit in the vast agro-ecology of the country. Even though Ethiopia lags behind many nations from the point of view of productivity of the crop considerable achievements were made possible. The overall success in the breeding program of soybean is reviewed in this article.